An evaluation of the rat intestinal monoamine biogeography days following exposure to acute stress - Bauer, Ella E.; Reed, Carter H.; Lyte, Mark; Clark, Peter J. (Frontiers in Physiology, 2022)
Stress-induced abnormalities in gut monoamine levels (e.g., serotonin, dopamine, norepinephrine) have been linked to gastrointestinal (GI) dysfunction, as well as the worsening of symptoms in GI disorders. However, the influence of stress on changes across the entire intestinal monoamine biogeography has not been well-characterized, especially in the days following stress exposure. Therefore, the aim of this study was to comprehensively assess changes to monoamine neurochemical signatures across the entire rat intestinal tract days after exposure to an acute stressor. To the end, adult male F344 rats were subjected to an episode of unpredictable tail shocks (acute stress) or left undisturbed. Forty-eight hours later rats were euthanized either following a 12 h period of fasting or 30 minutes of food access to evaluate neurochemical profiles during the peri- and early postprandial periods. Monoamine-related neurochemicals were measured via UHPLC in regions of the small intestine (duodenum, jejunum, ileum), large intestine (cecum, proximal colon, distal colon), cecal contents, fecal contents, and liver. The results suggest a relatively wide-spread increase in measures of serotonin activity across intestinal regions can be observed 48 hours after exposure to acute stress, however some evidence was found supporting localized differences in serotonin metabolization. Moreover, acute stress exposure reduced catecholamine-related neurochemical concentrations most notably in the ileum, and to a lesser extent in the cecal contents. Next, stress-related fecal serotonin concentrations were consistent with intestinal profiles. However, fecal dopamine was elevated in association with stress, which did not parallel findings in any other intestinal area. Finally, stress exposure and the food access period together only had minor effects on intestinal monoamine profiles. Taken together, these data suggest nuanced differences in monoaminergic profiles exist across intestinal regions the days following exposure to an acute stressor, highlighting the importance of assessments that consider the entire intestinal tract biogeography when investigating stress-related biological outcomes that may be relevant to GI pathophysiology.